Phased Linear Array of Circular Aperture Antennas - Hashim Abood, Ahmed (University of Thi-Qar Journal of Science, 2009)
In this paper the phased array consist of a circular aperture antennas are arranged in linear array to study the effect of the number of elements on the radiation pattern parameters. The effect of distribution of current on each elements also studied to reduced the side lobe level.